ChemInform Abstract: Acetal‐Initiated Prins Bicyclization for the Synthesis of Hexahydrofuro‐[3, 4‐c]furan Lignans and Octahydropyrano[3, 4‐c]pyran Derivatives. Issue 49 (9th December 2014) - Subba Reddy, B. V.; Ramana Reddy, M.; Sridhar, B.; Singarapu, Kiran Kumar
Abstract Compound (VII) is an analogue of allocolchicine.